Marketing strategy to increase sales volume using the AHP method in business XY Tebing Tinggi City - Syukriah; Sri Meutia; Andini Khairunisyah Siregar; Angela Prima Ranika (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
Business xy is one of the culinary industries typical of the city of Tebing Tinggi which operates in the bakery sector which is located in Rambutan District, Tebing Tinggi City, North Sumatra. Xy's business experienced a decline in sales due to increasingly fierce competition selling similar products and a decline in sales due to failure to implement appropriate marketing strategies. By considering these problems, to increase product sales volume, it is necessary to create a marketing mix strategy that uses the Analytical Hierarchy Process (AHP) method. This method will evaluate how consumers view the marketing mix features of peanut bread products. Apart from that, several alternative strategies will be given as references to be implemented in company xy, Tebing Tinggi City. The result of determining the marketing mix priority weights that must be applied to market products is that the strategy to increase market share (41%) focuses on the promotional mix. Alternative strategies that can be implemented include maintaining product quality as the main priority in the product mix (42%), setting prices with quality as the main priority in the product mix (31%), strategic sales locations (44%) as the main priority in the place mix, and increasing market share (44%) as the main priority of the venue mix, and increasing promotional activities on social media (35%) of the promotional mix